The visitor’s perception on environmental interpretation in underground cavities - Vale, Tatiane Ferrari do; Albani, Rafael Altoe; Moreira, Jasmine Cardozo (Geosaberes, 2019)
In ancient times humans used caves as a form of shelter. Currently, the use of these environments is also given by tourism in its various forms. Tourism in natural areas and environmental interpretation can help visitors understand the karst landscapes and contribute to their conservation. The objective of this study was to identify the perception of the visitors about the environmental interpretation in underground cavities. The methodology adopted was the application of an online questionnaire, from which 252 valid answers were obtained. The results point to an understanding of the interpretive tools’ use importance, and more than 90% of respondents believe that people are more connected with the environment, also considering that such visits lead to the formation of a scientific culture.